Beta-Hydroxybutyrate Enhances BDNF Expression by Increasing H3K4me3 and Decreasing H2AK119ub in Hippocampal Neurons - Hu, Erling; Du, Huan; Shang, Sen; Zhang, Yali; Lu, Xiaoyun (Frontiers in Neuroscience, 2020)
Neurological evidence suggests that beta-hydroxybutyrate (BHBA) has positive effects on the central nervous system. Previous studies have explored the molecular mechanisms by which BHBA affects different brain functions, but the effects of BHBA on epigenetic modifications remain elusive. Here, we showed that BHBA enhanced brain-derived neurotrophic factor (BDNF) expression by increasing H3K4me3 and decreasing H2AK119ub occupancy at the Bdnf promoters I, II, IV, and VI in hippocampal neurons. Moreover, BHBA treatment induced the upregulation of H3K4me3 and downregulation of H2AK119ub on the global level, both of which were dependent on the L-type calcium channel. Additionally, the BHBA-activated L-type calcium channel subsequently triggered the activation of Ca2+/CaMKII/CREB signaling, and promoted the binding of p-CREB and CBP to Bdnf promoters. These results indicate that BHBA regulates cellular signaling and multiple histone modifications to cooperatively modulate BDNF, suggesting a wide range of regulatory effects of BHBA in the central nervous system.